Method for coding DNA sequence and device and computer readability medium - AN DUNIN (2004)
本发明提供了一种编码DNA序列的装置和方法。一比较单元用于将已知DNA信息的参考序列和待编码的对象序列对齐，从而使两序列的一致碱基可以最优匹配，同时提取两序列间的差异信息。一转换单元用于将提取的参考序列和对象序列的差异信息转换为预定的字符串。一编码单元通过与存储于编码存储单元的单个字符相对应的预定转换编码来编码组成字符串的单个字符。一压缩单元通过常用的压缩方法压缩编码的结果。压缩结果存储于序列存储单元。 An apparatus and a method for encoding a DNA sequence are provided. A comparative unit aligns a reference sequence having known DNA information with a subject sequence to be encoded so that consensus bases of the two sequences are optimally matched and extracts a difference between the two sequences. A conversion unit converts information of the extracted difference between the reference sequence and the subject sequence into a string of predetermined characters. An encoding unit encodes the individual characters that make the string of the characters using predetermined conversion codes corresponding to the individual characters stored in a code storage unit. A compression unit compresses the encoded result using a common compression method. The compressed result is stored in a sequence storage unit.